The Cryosphere in a Changing Climate. Issue 15 (15th April 2014) - Pope, Allen; Baeseman, Jenny
<x xml:space="preserve">Abstract</x> The World Climate Research Programme (WCRP) Joint Science Committee has announced a series of "Grand Challenges, " calls to scientists to focus their research on areas that are important in understanding the climate system. One such area is the cryosphere in a changing climate. A 2012 draft white paper on this topic (http://www.climate‐cryosphere.org/media‐gallery/618‐gc‐cryo) served as the basis for a WCRP workshop held in mid‐October 2013 in Tromsø, Norway. The workshop centered on four themes: predictions and projections of polar climate; cryosphere model biases and shortcomings; ice sheet models, dynamics, and sea level rise; and permafrost and carbon for Earth system models.